An Ab Initio Study of Thermodynamic and Mechanical Stability of Heusler-Based Fe2AlCo Polymorphs - Martin Friák (Materials, 2018)
We use quantum-mechanical calculations to test a hypothesis of Glover et al. (J. Mag. Mag. Mater. 15 (1980) 699) that Co atoms in the Fe 2 AlCo compound have on average 3 Fe and 3 Co atoms in their second nearest neighbor shell. We have simulated four structural configurations of Fe 2 AlCo including the full Heusler structure, inverse Heusler polymorph and two other phases matching this idea. The highest thermodynamic stability at T = 0 K is indeed predicted for one of the phases with the distribution of atoms according to Glover and et al. However, small energy differences among three of the studied polymorphs lead to a disordered CsCl-structure-like (B2-like) phase at elevated temperatures. The fourth variant, the full Heusler phase, is predicted to be mechanically unstable. The global magnetic states are predicted to be ferromagnetic but local magnetic moments of Fe and Co atoms sensitively depend on the composition of the first and second coordination shells.